2014
DOI: 10.3748/wjg.v20.i26.8364
|View full text |Cite
|
Sign up to set email alerts
|

Experimental models of non-alcoholic fatty liver disease in rats

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in the Western world, and it persists at a high prevalence. NAFLD is characterised by the accumulation of triglycerides in the liver and includes a spectrum of histopathological findings, ranging from simple fatty liver through non-alcoholic steatohepatitis (NASH) to fibrosis and ultimately cirrhosis, which may progress to hepatocellular carcinoma. The pathogenesis of NAFLD is closely related to the metabolic syndrome and insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
0
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(172 citation statements)
references
References 101 publications
10
141
0
21
Order By: Relevance
“…The high-fat diet model has been widely used in previous NAFLD studies (39,40). The histological results of the present study observed NAFLD features in the model rats, indicating that an NAFLD model was successfully generated.…”
mentioning
confidence: 53%
“…The high-fat diet model has been widely used in previous NAFLD studies (39,40). The histological results of the present study observed NAFLD features in the model rats, indicating that an NAFLD model was successfully generated.…”
mentioning
confidence: 53%
“…Dietary-induced NAFLD rodent models, which vary in diet compositions, duration of feeding, animal strain, sex, and age, are the most widely used according to the previous studies (Kucera & Cervinkova 2014). A variety of genetic models of NAFLD are more expensive and less available (Qi et al 2005, Nagarajan et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…This animal model of steatosis was based mainly on the model reported by Delzenne et al (1997) with diet fed being MCDD instead of a high-fructose fat-free diet (Kucera & Cervinkova, 2014) because on using fructose alone liver inflammation does not occur in a pattern consistent with human fatty liver (Lee et al, 2007). UDCA, RSV, and NAC were dissolved in water and given daily by the oral route through an orogastric catheter at doses of 25, 10, and 20 mg/kg/d, respectively (Bujanda et al, 2008;Mas et al, 2008;Samuhasaneeto et al, 2007).…”
Section: Methods Of Steatosis Inductionmentioning
confidence: 99%